Assessing Employee’s Mental Wellbeing during Telecommuting - Estherita, S. Anisha; Vasantha, S. (Recent Research Reviews Journal, 2023)
Telecommuting has become the new norm because of COVID-19 pandemic which led to a national lockdown. Getting acquainted to the telecommuting took reasonable time for the employees as well as the employers. While nearly 90 percent of the employees worked from home, their wellbeing stood up as a concern for the employers. Maintaining the mental health of the employees has been a priority as only when the employees’ mental health is good, they will be able to contribute their best to the organisation even when they work from home. Accordingly, when employees are mentally healthy, they become engaged to their job and ultimately it enhances their job satisfaction. In congruence to this concern, this research aims to do an in-depth literature review on the impact of work from home or telecommuting on the mental wellbeing of employees. The study has been done using existing research articles retrieved from Google Scholar, Elsevier, and Academia. Due to the dearth of the studies made on COVID-19 and mental health, the recent studies made on this pandemic have been reviewed. The results indicate that telecommuting or work from home had a negative effect on the mental health of the employees. This research has also suggested a few ways to improve mental health of the employees during work from home.